2000
DOI: 10.1093/hmg/9.19.2853
|View full text |Cite
|
Sign up to set email alerts
|

Hyperammonemia with reduced ornithine, citrulline, arginine and proline: a new inborn error caused by a mutation in the gene encoding Delta1-pyrroline-5-carboxylate synthase

Abstract: delta(1)-pyrroline-5-carboxylate synthase (P5CS), a bifunctional ATP- and NADPH-dependent mitochondrial enzyme, catalyzes the reduction of glutamate to delta(1)-pyrroline-5-carboxylate, a critical step in the biosynthesis of proline, ornithine and arginine. Recently, we reported the cloning and expression of human and murine P5CS cDNAs. Previously, we showed that mammalian P5CS undergoes alternative splicing to generate two isoforms differing only by a 2 amino acid insert at the N-terminus of the gamma-glutamy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(152 citation statements)
references
References 19 publications
4
143
0
1
Order By: Relevance
“…Although the etiology of the severe neurocutaneous disorder in the family originally described by de Barsy remains unknown it was shown that de Barsy-like disorders can be due to mutations either in PYCR1 or ALDH18A1 [11,12,14,15]. In our patients, we found clinical features like facial dysmorphism, hypotonia, adducted thumbs and cutis laxa, which are frequently found in progeroid cutis laxa syndromes.…”
Section: Discussionmentioning
confidence: 47%
“…Although the etiology of the severe neurocutaneous disorder in the family originally described by de Barsy remains unknown it was shown that de Barsy-like disorders can be due to mutations either in PYCR1 or ALDH18A1 [11,12,14,15]. In our patients, we found clinical features like facial dysmorphism, hypotonia, adducted thumbs and cutis laxa, which are frequently found in progeroid cutis laxa syndromes.…”
Section: Discussionmentioning
confidence: 47%
“…Post-mortem genetic testing identified the m.8993T>G variant in the liver, muscle and blood with variant loads of 82-87% (Henriques et al 2012). Persistent hypocitrullinemia has been described in other mitochondrial disorders including Pearson syndrome (Ribes et al 1993), Leigh syndrome caused by isolated complex I deficiency (Debray et al 2010), mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes (MELAS syndrome) (Naini et al 2005), mitochondrial neurogastrointestinal encephalopathy (MNGIE) disease (Bindoff 2006), and with secondary mitochondrial respiratory chain dysfunction caused by organic acidemias (Atkuri et al 2009) and deficiency of mitochondrial pyrroline-5-carboxylate synthetase (P5CS) (Baumgartner et al 2000). In a small series of 16 Leigh syndrome patients, sensitivity and specificity of hypocitrullinemia as a marker for the m.8993T>G variant were reported to be 66% and 85%, respectively (Debray et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…21,22,38,42,43 The two patients, presented by Baumgartner et al, 22 showed low ornithine, arginine, citrulline and proline. Except for low ornithine levels in two of the patients described by Bicknell et al, 21 no amino-acid profile abnormalities have been described in the other patients.…”
Section: Metabolic Abnormalitiesmentioning
confidence: 95%
“…18 The similar and metabolically related P5CS deficiency (P5CSD) is caused by mutations in ALDH18A1. 21,22 Patients with DBS, or ARCL3, have CL, growth retardation, corneal clouding, athetoid movements and developmental delay. 23 Some children with a clinical diagnosis of DBS also carry mutations in the PYCR1 or ALDH18A1 genes.…”
Section: Introductionmentioning
confidence: 99%